Detection of Porcine Gelatin in Jelly Soft Candies Using Near-Infrared Spectroscopy and Chemometrics - Cendekiawan, Khrisna Agung; Wardhani, Firdha Aprillia; Anggraeni, Linda Suci; Anggraeni, Lutvi (Halal Science, 2025)
Gelatin, commonly used in jelly soft candies, is often derived from porcine sources, which Islam prohibits. This study developed a rapid and reliable method for detecting porcine gelatin using near-infrared (NIR) spectroscopy combined with chemometric analysis to support halal verification. Twenty samples were analyzed: 10 with 100% bovine gelatin and 10 containing 10–100% porcine gelatin. Spectral data were processed using partial least squares (PLS) regression and linear discriminant analysis (LDA). The PLS model showed high predictive accuracy (RMSEC = 2.87, R²cal = 0.9931; RMSEP = 0.0124, R²val = 0.9919), while LDA classified samples with over 90% accuracy. Results were consistent with the Xema Pork Detection Kit, confirming the method’s reliability. This approach offers a fast, accurate tool for halal compliance in food products.